Hacia una sociología de la pobreza : la relevancia de las dimensiones culturales - Bayón, María Cristina (El Colegio de México, 2013)
mensions affect both the relations between social classes, the public discourse on poverty, the representations and experiences, as policies and institutions that emerge in relation to it. In the contemporary debate on poverty, while recognizing their importance, these dimensions have not been suffi ciently explored in the literature on the subject. In order to investigate possible routes theoretical and empirical implications for their approach, we analyze the concepts of frames and cultural repertoires, symbolic boundaries, narratives and cultural capital, emphasizing its use in various poverty researches. The potential of these concepts lies in its openness to account for the heterogeneity of experiences, meanings and possible responses against similar structural constraints, allowing remove the stigmas and stereotypes about “the poor” and “their culture” emerging from the thesis of the “culture of poverty”. Finally, we emphasize the need to inquire about the mechanisms by which cultural dimensions contribute to generate and reproduce inequality in a particular society.